ANALYSIS OF DOMINANT FACTORS AFFECTING THE IMPLEMENTATION OF COVID-19 SCREENING AT TGK CHIK DITIRO SIGLI HOSPITAL - Ismuntania, Ismuntania; Kartika, Kartika (Universitas Islam Negeri Alauddin Makassar, 2021)
Introduction : The implementation of the Covid 19 screening is very important to control the spread of the Corona Virus which is increasingly rampant. Screening is the first step that must be carried out on all suspected people including every hospital visitor. In principle, all visitors should be screened even if they are asymptomatic because some infected cases do not show any symptoms. The purpose of the study: to analyze the dominant factors that influence the implementation of Covid 19 screening at Tgk Chik Ditiro Sigli Hospital. The stages of this research are starting from the preparation, implementation, and analysis stages. The design used is a quantitative design with a causal association approach, which is to see a causal relationship. The method of data collection was done by distributing questionnaires and then analyzed using multiple linear regression statistical analysis. The next step is to present the data and draw conclusions. The results of this study were found that the factors of officers, patients, PPE, policies, and the environment affected the implementation of the Covid 19 screening with p-values of 0.001, 0.000, 0.002, 0.001, and 0.002, respectively. The most dominant factor influencing is the officer factor with the results of univariate analysis, namely Y = 19,877 + 0,091X1 + 0,045X2 + 0,080X3 + 0,043X4 + 0,072X5. This study concludes that the officer factor is the most dominant factor influencing the implementation of Covid 19 screening.